2011
DOI: 10.1136/hrt.2011.225193
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan reduces neointima volume and pulse wave velocity 8 months after zotarolimus-eluting stent implantation in hypertensive type 2 diabetic patients

Abstract: Telmisartan reduced neointima volume; atherosclerosis progression 10 mm proximal and distal to the stented segment and baPWV independent of blood pressure, glucose and lipid control in hypertensive type 2 diabetes. Clinical trial no NCT00599885 (clinicaltrials.gov.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…28 It was also reported that telmisartan reduced neointima volume of coronary plaque and brachial-ankle pulse wave velocity 8 months after zotarolimus-eluting stent implantation in hypertensive type 2 diabetic patients. 29 In the present study, however, 6-month angiographic follow-up showed no significant differences in percent diameter stenosis and binary restenosis rate of the in-stent culprit lesions between the 2 groups. Regarding the effects of telmisartan, local anti-inflammatory and anti-arteriosclerotic effects in non-culprit lesions were independent of in-stent restenosis in culprit lesions at 6-month follow-up.…”
Section: Discussioncontrasting
confidence: 48%
“…28 It was also reported that telmisartan reduced neointima volume of coronary plaque and brachial-ankle pulse wave velocity 8 months after zotarolimus-eluting stent implantation in hypertensive type 2 diabetic patients. 29 In the present study, however, 6-month angiographic follow-up showed no significant differences in percent diameter stenosis and binary restenosis rate of the in-stent culprit lesions between the 2 groups. Regarding the effects of telmisartan, local anti-inflammatory and anti-arteriosclerotic effects in non-culprit lesions were independent of in-stent restenosis in culprit lesions at 6-month follow-up.…”
Section: Discussioncontrasting
confidence: 48%
“…In this study, adiponectin, which is involved in various metabolic processes and which influences neointimal hyperplasia after coronary stenting, increased significantly only in the pioglitazone group. 20 Adiponectin stimulates nitric oxide production in endothelial cells and blunts the secretion of TNF-α from macrophages and the ensuing expression of adhesions on the endothelium, thereby inhibiting several essential steps of neointimal proliferation. 31 Adiponectin, in turn, has been shown to decrease cytokine production from macrophages and to interfere with TNF-α signaling, thereby reducing inflammatory conditions after stent implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Balloon angioplasty and stent implantation were performed according to standard clinical practice, as described previously. 20 OCT data were analyzed at the Korea University OCT Core Laboratory, and all OCT data were analyzed by individuals who were unaware of the treatment assignments. OCT was performed after 200-μg i.c.…”
Section: Coronary Angiography and Octmentioning
confidence: 99%
“…[32][33][34] Moreover, it has been reported that pharmacologic therapy with ACE-I or ARB reduced neointima proliferation and restenosis after stent implantation. [35][36][37] It was speculated that the tissue renin-angiotensin system inside the stent may play a role in neointima formation. However, the impact on late stent complication, such as stent thrombosis and late restenosis, has not been investigated.…”
Section: The Use Of Ace-i/arb and Namentioning
confidence: 99%